Education, Leadership and Business Ethics
XIX, 323 p.
Keywords: Education, Leadership and Business Ethics: New Essays on the Work of Clarence Walton includes a history and anecdotes of Clarence Walton's professional and personal life; a discussion of the controversial introduction of ethics into the field of management studies; contributions on a variety of subjects connected to leadership and business ethics from experts in the field; and critical essays reviewing Clarence's most recent work in social criticism. The book gives a history of the rise of the fields of business and society and business ethics, details the events leading to its acceptance in academic circles and gives personal accounts by Clarence Walton, one of the people most responsible for its creation. Intended target groups are students, former academic peers, and friends of Clarence Walton, as well as anyone interested in the history of business ethics or connected to Columbia University of America, or The American College.